Reinvesting or Consuming Dividends: Account Structure Matters - Müller-Dethard, Jan; Reinhardt, Niklas; Weber, Martin (Review of Finance, 2025)
Abstract It is a long-standing fact that households mostly consume and rarely reinvest dividends. Among representative brokerage clients of one of Germany’s largest banks, we find the opposite: 80 percent reinvestments and 12 percent consumption. Of these reinvestments, the majority occurs with a delay after dividends are initially parked as brokerage cash. Motivated by this finding, we study payout modalities (deposits into brokerage accounts, checking accounts, or checks) as a novel mechanism that nudges investors toward reinvesting or consuming dividends. Consistent with a transition from checks to brokerage deposits, we find that the dividend consumption rate in the Consumer Expenditure Survey has decreased substantially over time.